Strategi Pimpinan Asrama dalam Mengembangkan Karakter Mandiri Siwa SMP Negeri 2 Sawahlunto - Septi Gia Aprima; Suswati Hendriani (Journal on Education, 2025)
The research aims to explore the strategies employed by dormitory leaders in developing students' self-reliance at SMP Negeri 2 Sawahlunto. The study adopts a qualitative case study approach with data collected through observation, interviews, document analysis, and triangulation to ensure data validity. Findings reveal that the strategies implemented by dormitory leaders at SMP Negeri 2 Sawahlunto in fostering students' self-reliance are centered around structured planning, thorough needs analysis, and holistic program implementation. Planning begins with specific and measurable goals aligned with core values such as honesty and responsibility. Needs analysis involves active participation from students, parents, teachers, and dormitory staff, supporting character development through a variety of intracurricular and extracurricular activities. These strategies aim to create a dormitory environment that nurtures students' independence, leadership, and social responsibility, contributing to broader educational objectives.